﻿Rethink ﻿Responsibility in the Age of AI - de Vaujany, François-Xavier; Leclercq-Vandelannoitte, Aurélie (MIT Sloan Management Review, 2026)
As AI systems take on more organizational decision-making, traditional models of accountability — focused on identifying a single culprit when something goes wrong — are breaking down. Drawing on recent research, the authors introduce narrative responsibility, a framework that maps the real story behind failures, distributes ownership across teams, and embeds ongoing reflection into everyday practice. This approach is essential for organizations navigating the complexity of AI-enabled decisions.